Anuj Kumar , Randhir Singh , Satyavir Singh , Sendhil, R. , Ramesh Chand and JK Pandey - Anuj Kumar , Randhir Singh , Satyavir Singh , Sendhil, R. , Ramesh Chand and JK Pandey, (Indian Journal of Extension Education, 2017)
The study was conducted in Kaithal district of Haryana during 2014-15 in nine villages with 120 purposively selectedfarmers who have adopted either of the three resource conservation technologies viz; zero tillage, rotary tillage and laserland leveller or in combination. Majority (68.98 %) of the farmers belonged to middle age group (31-50 years) followedby young (20.33 %) and old (18.69 %). Majority (85 %) of the farmers were literate and agriculture was their mainoccupation. Farmers were categorised in four groups on land holding basis and 6.5 per cent, 15.46 per cent, 39.02 per centand 39.02 per cent, in marginal, small, medium and large categories, respectively. In the study area, majority of thefarmers preferred Agriculture Development Officers (ADOs) as main source of information. The study on adoptionpattern of resource conservation technologies revealed that 69.92 per cent of the farmers had adopted zero tillage, 51.22per cent rotary tillage, 67.48 per cent laser land leveller, 22.76 per cent zero tillage+rotary tillage, 47.15 per cent zerotillage+laser land leveller, 33.33 per cent rotary tillage+laser land leveller and 13.01 per cent zero tillage+ rotary tillage+laser land leveller. Majority (84.88 %) of the farmers used zero tillage for timely sowing and 40.70 per cent used for bothi.e. timely and late sown conditions. Regarding the impact of zero tillage technology, majority of the farmers (77.91 %)told that there was saving of time under zero tillage sowing as compared to conventional tillage. Majority of the farmers(80.23 %) told that there was an increase in broader leaf weeds under zero tillage and reduction in narrow leaf weedpopulation (80.23 %) and 76.74 per cent of them recorded reduction in overall weed population. All the farmers agreedthat there was cost saving under zero tillage technology. Most of them (91.86 %) harvested more yield as compared toconventional tillage. A large number of farmers (61.63 %) observed longer crop duration (4-7 days), increased soilfertility (51.16 %), increased organic carbon in the soil (54.65 %) and increased moisture retention capacity of soil (50%) and less lodging (87.21 %) as compared to conventional tillage. All the farmers agreed that there was time savingunder rotary tillage in wheat sowing. Majority of them (68.25 %) recorded decrease in cost of cultivation, more yield(41.27 %), increased soil fertility (86.96 %), increase in organic carbon content of soil (57.14 %), increase in moistureretention capacity of soil (52.33 %), avoidance of terminal heat (85.71 %) and increase in lodging (46.03 %). Due toadoption of laser land leveller farmers (45.78 %) could save time in field preparation, 2-3 per cent increase in cultivablearea, less time required to irrigate the crop, 30-40 per cent water saving, more yield (96.39 %) and less lodging (95.18 %).